2016
DOI: 10.1590/1516-3180.2015.02691801
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioidomycosis in the spine: case report and review of the literature

Abstract: CONTEXT: Paracoccidioidomycosis is a systemic form of mycosis that spreads hematogenously, secondarily to reactivation of lung infection or infection at another site or to new exposure to the causative agent. Few cases of bone involvement have been reported in the literature and involvement of the spine is extremely rare. CASE REPORT: We describe a case of a 68-year-old male patient with spondylodiscitis at the levels L4-L5 caused by presence of the fungus Paracoccidioides brasiliensis, which was diagnosed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…PCM is found from southern Mexico to northern Argentina and especially in Brazil, where the greatest number of cases have been reported (San-Blas et al, 2002; Colombo et al, 2011; Hernández et al, 2011; Alvarenga et al, 2016). Human infection by Paracoccidioides spp.…”
Section: Introductionmentioning
confidence: 99%
“…PCM is found from southern Mexico to northern Argentina and especially in Brazil, where the greatest number of cases have been reported (San-Blas et al, 2002; Colombo et al, 2011; Hernández et al, 2011; Alvarenga et al, 2016). Human infection by Paracoccidioides spp.…”
Section: Introductionmentioning
confidence: 99%
“…Gamaletsou Immunosuppression from hormone, chemotherapeutic agents used for oncologic and autoimmune diseases, hemodialysis and organ transplantation is a risk factor for mycosis. Immunodeficiency caused by HIV is another contributing factor [11][12][13][14][15][16][17]. The studies performed by the International Working Group on the Diabetic Foot showed that mycosis was detected along with bacterial flora in some diabetic patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Pathomorphological examination of biopsy sample at the nidus of purulent infection is the basic diagnostic criterion. Diagnostic biopsy can be produced as part of preoperative preparation of the patient [9][10][11][12][13][14][15][16][17]. Risk grading scale for mycosis was developed with the above factors in mind marking presence/absence of the signs in the right-hand column (Table 9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations